Sustainability of two--tier co-operatives in Bangladesh: a study on co-operatives under rural development : I project in Bogra district. - Rahman, Md. Mushfiqur (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2006.